Infrared optoelectronics devices and applications - Nunley, William (Optical engineering (Marcel Dekker, Inc.), 1987)
Written in an easy-to-read style that answers the needs of engineers and facilitates quick comprehension of a wealth of technical data and concepts, Infrared Optoelectronics is an essential source for optical, design, and electrical and electronic engineers.